Effects of phenology and the microclimate on the seed set of Anemone nemorosa - Risser, Laurent (SLU/Dept. of Ecology, 2016)
Changing climate affects the dispersal and phenology of plants and pollinators. Particularly in the spring, climate warming accelerates the timing of flowering and insect emergence. Temporal mismatch is a fairly well studied biological phenomenon. Nevertheless the phenomenon has been studied only for a small number of systems and organisms, and more empirical evidence to show that mismatch occurs and how it is affected by changes in environment. The lack of studies that directly address the effects of this type of phenological mismatches on plant seed set makes it difficult to predict how plant reproductive output will be affected. Although it is reasonable to assume that the reduced seed set is a general response. This response varies greatly among species, which highlights the need for better empirical data. In current the study, the aim is to investigate how the microclimate and flowering time can have an impact on the seed set. The effect of the pollinator on the seed production in a wild flower (Anemone nemorosa) was measured at two different flowering times. Three treatments (a) self-pollination (b) hand-pollination and (c) wild-pollination, were applied during both flowering times: one in mid of April (early spring) and the other in early May (late spring). Pollinator abundance was measured at all the experimental sites and the seed sets were counted in collected flowers. The results show that the flowering time has significantly affected the fertile seed production. However microclimate did not had significant effect fertile seed production. Moreover, during the both flowering times, the variation in the abundance and diversity of the pollinator were not detected, thus the microclimate has an effect on the abundance and diversity of pollinator. There was no significant relationship between the pollinator diversity, abundance and seed set. In conclusion, flowering significantly affects the production of seed set in Anemone nemorosa.